PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA GURU - Muhamad Andri Kurniawan; Sardiyo Sardiyo; Fitria Fitria (Jurnal Interprof, 2025)
This study aims to explore the role of transformational leadership of school principals in improving teacher performance at SMPN Purwodadi. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through observations, interviews, and documentation involving the principal, vice principal, and six teachers. The results revealed that the four dimensions of transformational leadership— idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—were effectively implemented, significantly contributing to the improvement of teacher performance. This research affirms that transformational leadership style is a productive approach to fostering a supportive work environment and encouraging professional growth among teachers.